The Post-tenure Apex: Unrewarding, Unproductive, Unhappy. Is Continuing Learning a Remedy for Mid-Career Misery? - Heather Kanuka; Jonathan Anuik (Ali Khorsandi Taskoh, 2021)
Academics who are in mid- to late-stages of their career are often overlooked as participants when leaders of higher education are planning continuing learning opportunities. The reasons are varied but typically originate from a lack of understanding about this long and important phase in an academic's career. Prior research has reported that a crisis can happen at this career apex, illustrating a need for continuing learning. Many academics who move into mid-career encounter issues such as plateauing (e.g., no longer finding new research results), career disappointments (e.g., no longer able to attain research funding), and changing perspectives about their priorities (e.g., publication outputs are no longer a priority). The purpose of this study was to extend our understanding of the value of continuing learning for mid- to late-career faculty. We conducted a study on the perceived value and impact of continuing learning for mid- to late-career academics. Our findings indicate that when development centres are planning activities for mid- to late-career faculty, it will have the greatest value when (a) based on career-stage appropriate needs (e.g., high priority areas identified); and (b) activities are directed to mid- to late-career academics. While prior research has shown that interaction and collaboration are important for mid- to late-career academics, findings from this study indicate technical and practical knowledge are a higher priority.